CHATGPT FOR DEVELOPING CRITICAL THINKING IN WRITING: PERSPECTIVES OF SENIOR HIGH SCHOOL ENGLISH TEACHERS IN INDONESIA - Anam, Khoirul; Rowiyah, Siti; Hendro Wicaksono, Bayu; Wahyu Setyaningrum, Rina; Lestiono, Riski (English Review: Journal of English Education, 2025)
The use of ChatGPT as a generative artificial intelligence (AI) has been increasingly integrated into daily communication as a complimentary chatbot that assists individuals in resolving inquiries. ChatGPT's ease is also being discussed in the educational context, including in language teaching. Although previous studies have examined the use of artificial intelligence in English language teaching, limited studies investigate the possibilities and constraints of ChatGPT in enhancing students' critical thinking abilities in writing from the educators' viewpoint, especially senior high school level educators. Therefore, this study examines English teachers' perspectives on utilizing ChatGPT to improve students' critical thinking skills in English writing sessions. Employing a mixed-method design, insights were obtained from qualitative data of interviews with six teachers and triangulated with quantitative survey responses from 20 teachers. Findings reveal the teachers' recognition of ChatGPT's ability to facilitate individualized learning and improve instructional effectiveness. However, there are remaining concerns that educators are apprehensive about, particularly regarding the students' overdependence on AI, which may hinder the advancement of critical thinking abilities. This study offers a framework for the efficient use of AI tools in L2 instruction to enhance students' critical thinking skills, providing valuable recommendations for instructors aiming to align technological improvements with pedagogical principles. Further research utilizing larger sample sizes in an experimental context should be conducted to yield more robust conclusions.